Takaful insurance in Algeria : a study in the light of executive decree n° 21-81 - Abbas, Karima (Journal of Human Sciences, 2022)
We have tried to highlight the legal system of Takaful insurance in Algeria as a new type of insurance. It has emerged as a legitimate alternative to commercial insurance. Article 103 of law n° 19-14 relating to the finance law for the year 2020 allowed its exercise. However, the terms and conditions of his function were only determined after the promulgation of Decree No. 21-81.This decree removed the ambiguity of this type of insurance, thus paving the way for investors wishing to work in the field of Islamic insurance, thus creating Takaful companies. It also granted insurance companies operating in the national market the possibility of practicing this type of insurance by opening windows.This is an effort by the Algerian legislator and public authorities to advance the insurance sector, by diversifying its products, in order to satisfy all strata of society.